1978
DOI: 10.1080/00288233.1978.10427463
|View full text |Cite
|
Sign up to set email alerts
|

Response surfaces of semidwarf wheat for seeding rate, and levels and times of application of nitrogen fertiliser

Abstract: A three factor central composite second order design in incomplete blocks was used to quantify the responses of semidwarf 'Karamu' wheat established at five seeding rates (170-580 seeds/m 2 ), and fertilised at five rates of N at the onset of tillering (0-124 kg/hal and during spikelet growth (0-38 kg/ha). N applied at tillering raised grain yields by increasing spike populations and the mean number of spike lets per spike, but generally depressed mean grain dry weights and, at low rates, reduced grain content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…In this work the relationship between grain yield and its components was similar to that discussed by Scott et al (1975), Dougherty et al (1974Dougherty et al ( , 1978Dougherty et al ( , 1979, and Nourafza & Langer (1979). The most significant component of grain yield, up to an optimum population, which differed for the two soil types, was ear number at maturity.…”
Section: Discussionsupporting
confidence: 72%
“…In this work the relationship between grain yield and its components was similar to that discussed by Scott et al (1975), Dougherty et al (1974Dougherty et al ( , 1978Dougherty et al ( , 1979, and Nourafza & Langer (1979). The most significant component of grain yield, up to an optimum population, which differed for the two soil types, was ear number at maturity.…”
Section: Discussionsupporting
confidence: 72%
“…Kopara produced about one more spikelet per spike than the semidwarf (Dougherty et al 1978), probably because Kopara reached the 2'0…”
Section: Spikelets Pet Spikementioning
confidence: 93%
“…Similar treatments were incorporated in a factorial arranged in randomised blocks to compare the efficiencies of these designs in agronomic experimentation. Results obtained for the factorial design have already been published (Scott 1978), and information we obtained on Karamu and on relative efficiencies has been summarised (Dougherty et al 1978). In this paper we present results for Kopara and compare its responses to that of Karamu.…”
Section: Introductionmentioning
confidence: 96%
“…Nitrogen generally improves yield by increasing ear density and number of grains per ear, i.e. the number of grains per m 2 , whereas grain weight only varies slightly (Dougherty, 1978;Darwinkel, 1983;Siddique, 1989;Gooding & Davies, 1997). Darwinkel (1983) found that the maximum effect on: (1) Tiller formation and spikelet initiation occurred when N was supplied at the beginning of tillering (GS21); (2) number of shoots with ears when N was given at the beginning of stem elongation (GS30); (3) number of fertile flowers per spikelet, grains per fertile spikelet and ultimately grains per ear when N was applied during stem elongation until flag leaf emergence (GS30-39); and (4) grain weight when N was given at ear emergence (GS47).…”
Section: Introductionmentioning
confidence: 98%